The quest for the origins of Vedic culture : the Indo-Aryan migration debate - Bryant, Edwin F. (Edwin Francis), 1957- (Oxford University Press, 2001)
This work studies how Indian scholars have rejected the idea of an external origin of the Indo-Aryans, by questioning the logic assumptions and methods upon which the theory is based.